Preferensi Konsumen terhadap lkan Tawar dan lkan Laut di Pasar Tradisional Bauntung Kota Banjarbaru - Syahida Rakhmah Apasha; Nuri Dewi Yanti; Rifiana Rifiana (Universitas Lambung Mangkurat, 2015)
The fisheries sector has an important role in the economy . The sector also provides benefits in supplying nutritious food to the Indonesian people . Broadly speaking, the nutrient cont ent of both types of freshwater fish and marine fish is rich in protein and vitamins. The study determines the preferences of society and describes the attributes that most consumers consider in the decision to buy freshwater fis h or marinefish i n the Bauntung Market, Banjarbaru. The consumer preference in the type fre shwater fish is higher that the marine fish. The attributes that consumers consideredin the purchase decision are income and the number of family members.